Compensating victims of a European Deepwater Horizon accident: OPOL revisited. (December 2015) - Faure, Michael; Wang, Hui
Abstract: The introduction sketches the importance of the Deepwater Horizon incident that occurred five years ago on 20 April 2010 in the Gulf of Mexico. The question central to this contribution is how compensation would be provided if such an incident were to occur in European waters. A mechanism that plays an important role in Europe, more particularly for the North Sea is the Offshore Pollution Liability Association Limited, referred to as OPOL.Section 2 introduces OPOL by elaborating the origins, main features, membership rules, financial responsibility and claims handling.Section 3 discusses OPOL in the UK regulatory environment which is particularly interesting since OPOL membership in the UK is mandatory.Section 4 provides a critical analysis by first describing the practice of OPOL and next discussing the advantages and limits of this particular scheme.Section 5 discusses which insurance and financial instruments are used in Europe in areas where OPOL does not apply. In turn self-insurance, (re)insurance as well as risk-pooling schemes are discussed. FinallySection 6 examines to what extent it would be possible to expand OPOL either in amount or in geographical scope (more particularly beyond the North Sea).Section 7 concludes.